4x-13x+10=0

Simple and best practice solution for 4x-13x+10=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-13x+10=0 equation:


Simplifying
4x + -13x + 10 = 0

Reorder the terms:
10 + 4x + -13x = 0

Combine like terms: 4x + -13x = -9x
10 + -9x = 0

Solving
10 + -9x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10' to each side of the equation.
10 + -10 + -9x = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -9x = 0 + -10
-9x = 0 + -10

Combine like terms: 0 + -10 = -10
-9x = -10

Divide each side by '-9'.
x = 1.111111111

Simplifying
x = 1.111111111

See similar equations:

| -10h=-6(4+3h) | | .5xn=.333 | | 6x+2y=16.60 | | 4(5)-4x=4 | | -4k(k+6)-(9k-6)=-14k | | 3x+2.5x=60 | | P=2(1.08)t | | 4.9t^2+17.9t+5=0 | | 12.8*0.25= | | X-90=4x | | 5a=7+8a | | 4x-2(x-4)=-6+4x+10 | | (10x^2+30x)=(2x^2-30x-75) | | -2x+5(-2x-6)=18 | | 3-(6s-15)=4s+8 | | 20x^2+25x+75=0 | | 3x+3=x-18 | | -16=x-10 | | 24-6k=6(k-4) | | 0.4y+0.65x=60 | | 24-6k=6k(4-k) | | 6(1+4a)=-114 | | 3(9y+3)-9=2y+21 | | 39+0.75x=x | | (4z+2)+(5z-3)= | | T*4-3=12 | | 5x^2+10x+46=0 | | 14=-0.5x^2+46 | | 3(4x-1)=9x+6 | | 18x-6=20x-12 | | A*5+6=10 | | -30de+12=18d |

Equations solver categories